Variation in leisure sport conflicts and coping strategies depending on participation type and proximity during the COVID-19 pandemic - Kim, Young-Jae; Shin, Kyu-lee; Kang, Seung-Woo (Frontiers in Public Health, 2023)
Introduction New conflict types have arisen in leisure sports activities due to social regulations designed to address COVID-19. We analyze the differences in conflict-inducing factors and coping strategies across various types of leisure sports and levels of spatial proximity. Methods Korean adults aged between 20 and 60 years, who had participated in leisure sports activities since the COVID-19 outbreak in January 2020, were surveyed, and 508 responses were collected for analysis. The differences in leisure sports conflicts and coping strategies across the types of leisure sports participation and spatial proximity were tested. Results The results show that conflict due to prejudice was higher in typical indoor sports activities, such as Pilates, yoga, and gym workouts, whereas conflict due to competition or not observing etiquette was higher in indoor golf. Second, conflict due to prior expectations and prejudice was high in outdoor sports activities, such as jogging and hiking. Finally, all participants showed avoidance behavior, but it was observed more frequently in outdoor sports than indoor sports. Discussion The study reveals how much leisure conflict is induced by various types of leisure sports participation, particularly during outdoor activities, which usually feature a relatively low density of participants. It underscores the necessity of developing structural approaches to resolving leisure conflicts in dangerous spaces or requiring intensive management and creating new leisure sports activities.